AC-DC PFC Converter Using Combination of Flyback Converter and Full-bridge DC-DC Converter - Efendi, Moh. Zaenal; Rizal, Abdul; Erzanuari, Aldi; ., Suryono; Windarko, Novie Ayub (EMITTER International Journal of Engineering Technology, 2014)
This paper presents a combination of power factor correction converter using Flyback converter and Full-bridge dc-dc converter in series connection. Flyback converter is operated in discontinuous conduction mode so that it can serve as a power factor correction converter and meanwhile Full-bridge dc-dc converter is used for dc regulator. This converter system is designed to produce a 86 Volt of output voltage and 2 A of output current. Both simulation and experiment results show that the power factor of this converter achieves up to 0.99 and meets harmonic standard of IEC61000-3-2.Keywords: Flyback Converter, Full-bridge DC-DC Converter, PowerÂ Factor Correction.